Coastal protection with submerged vertical flexible sheets - Toh, Yong Jia (Nanyang Technological University, 2021)
This study investigated the wave interactions with submerged vertical polypropylene (PP) sheets experimentally. The sheets with different lengths were tensioned and hinged at both ends. In addition, the study used the GoPro camera to record the wave measurement. Furthermore, the cameras and the image processing toolbox from MATLAB captured and identified the wave interaction with the sheet. Based on the results, the reflection coefficient was identified by the least square method. At the same time, the amplitude of the transmitted wave was identified as the average wave amplitude of transmitted waves. The results show that increased tension leads to increased rigidity which causes more reflected wave energy. Therefore, it had a higher reflection coefficient and lower transmission coefficient. When the wave period was near the sheet resonance frequency, there was a sudden increase in the transmission coefficient. In addition, the wave interactions with fully and partially tensioned penetrated sheets are discussed based on reflection and transmission coefficient and maximum sheet displacement. Further studies with different length of sheets and tension forces applied on the sheet need to be investigated in the future.